x=tanh(x)

Simple and best practice solution for x=tanh(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=tanh(x) equation:


Simplifying
x = tanh(x)

Multiply ahnt * x
x = ahntx

Solving
x = ahntx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1ahntx' to each side of the equation.
-1ahntx + x = ahntx + -1ahntx

Combine like terms: ahntx + -1ahntx = 0
-1ahntx + x = 0

Factor out the Greatest Common Factor (GCF), 'x'.
x(-1ahnt + 1) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-1ahnt + 1)' equal to zero and attempt to solve: Simplifying -1ahnt + 1 = 0 Reorder the terms: 1 + -1ahnt = 0 Solving 1 + -1ahnt = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1ahnt = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1ahnt = 0 + -1 -1ahnt = 0 + -1 Combine like terms: 0 + -1 = -1 -1ahnt = -1 Add 'ahnt' to each side of the equation. -1ahnt + ahnt = -1 + ahnt Combine like terms: -1ahnt + ahnt = 0 0 = -1 + ahnt Simplifying 0 = -1 + ahnt The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| x-4.2=6 | | 12.67(a-3)=.5 | | 1.4y=7 | | -6(4x-3)+5(5x-4)-8=7-8 | | 2(y-2)-4=10 | | 2x^2-5x+245=0 | | -3n+9=-4n+5 | | 3X+4-5X=-10 | | 12x^4+x^2-6=0 | | 60+2x=7(x+60) | | X^2+y^2+Z^2=50 | | -3n+9=-4+5 | | 60+2x=7(x+30) | | 3d+8=2(d+4) | | x+3.5=2.15 | | 14+4p=5p | | -3.8x=51.68 | | 8xy-8y+yx-y= | | 5(x-2)=34 | | y=5sin(5x+20)-2 | | -27x=39.15 | | 8-3x+8=3+4x | | a*3-8=19 | | 28-10x=12+6x | | x-7.2=-4.4 | | -(y+4)=36 | | X+4=4(1-X)+5x | | .65x=25 | | -6t=60+10t | | N=8*3.14 | | 4.5x-1=3.5x | | 9x-8=9x |

Equations solver categories